ANTIBACTERIAL EFFECTIVENESS (Propionibacterium acnes) OF KOMBUCHA FACE TONER FORMULA WITH GREEN TEA LEAF (Camellia sinensis L.) - Aprilia Fatma Ely; Shelly Taurhesia; Teti Indrawati (Medical Sains : Jurnal Ilmiah Kefarmasian, 2023)
Acne is a process of chronic inflammation of the sebaceous glands in the skin caused by the bacteria Propionibacterium acnes. Approximately 80-100% incidence of acne occurs in adolescents. One solution is to use an antibacterial agent called catechins. It can be easily obtained from green tea, which has high catechin content. The amount of catechins used as antibacterial substances in green tea can also be increased by fermentation. In addition, lactic acid-fermented green tea can inhibit the growth of P. acnes. This study aimed to produce green tea kombucha face toner with anti-acne activity and good physical stability. This study included an experimental research. The research population was in the form of antibacterial compounds in face toner. The sample was green tea kombucha, which showed antibacterial activity at a concentration of 50% with an 18 mm Diameter of Inhibition Zone (DIZ). And the best formula is F1 with 0.84 mm DIZ, has a pH of 4 which is safe for the skin, clear solution, has clean power, it is also stable during storage at 30o and 40oC, but it has a rather disagreeable scent of toner. Keywords: Acne, Antibacterial, Green Tea Leaves Kombucha, Face Tone